Limosilactobacillus reuteri Y15 enhances uterine development and function in gilts via the gut-uterus axis - Juanli Huo; Shen Li; Dongxin Lu; Lei Li; Weidong Zhang; Yukang Li; Bin Yao; Yong Zhao; Yawei Zhang; Jie Zhang; Huiying Luo (Theriogenology, 2026)

Synergistic enhancement of microalgal fatty acids via Batch Bayesian Optimization-driven combinatorial additive engineering - Yu Zhao; Yawei Wu; Guopeng Chen; Shi Guo; Fangzhong Wang; Lei Chen; Weiwen Zhang; Jie Chen (Bioresource Technology, 2026)

Aptamer/magnetic-MIP dual-recognition sandwich biosensor for rapid and recyclable determination of kanamycin in food - Tingting Wang; Fengjuan Zhao; Zhiguang Suo; Yong Liu; Yawei Huang; Min Wei (Analytica Chimica Acta, 2026)

Nitrogen-doped pyrite composite for enhanced Fe(III)/Fe(II) cycling and broad-spectrum pollutant degradation via peroxymonosulfate activation - Yan Yan; Zhenjie Li; Chunwei Liu; Yuan Qiao; Caiping Hu; Longquan Zhang; Xiaoguo Shi; Yizhe Zhao; Yawei Gu; Wenyu Wang (Process Safety and Environmental Protection, 2026)

Robust water matrix tolerance for selective photocatalytic detoxification and decarboxylation of D-Glu and D-MeAsp in microcystin-LR via nanoconfinement-mediated active site regulation - Chengzhuo Yu; Jin Xu; Silong Wang; Li Xiong; Fanglan Geng; Yarui Wang; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2026)

Light-triggered molecular lever in a MOF@COF nanosheet for synergistic enhancement of heat and mass transfer in CO2 photothermal desorption - Jingyu Bao; Mingjie Zhou; Zuxue Bai; Yawei Xie; Xuehui Jia; Jiajun Zeng; Yujie Huang; Ruimeng Wang; Jianmin Chen; Zhaowei Jia; Liqin Zhou; Zhongxing Zhao; et al. (Chemical Engineering Journal, 2026)

Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

Multi-mode and encapsulated droplet-based electricity generator for environmental sensing and cathodic protection - Miaomiao Cui; Peiyu Wu; Ruiqi Fang; Wenbo Zhao; Yuankai Jin; Yawei Feng; Fuhui Wang; Zhipeng Zhang; Xiangyu Li; Dake Xu (Chemical Engineering Journal, 2026)

A portable source-informed machine learning framework for predicting heavy metals in legacy smelting sites with strong spatial heterogeneity - Xu Cao; Yan Liang; Yawei Zhao; Tianhuan Chen; He Huang; Tian Xie (Journal of Hazardous Materials, 2026)

Revealing the protein dynamics of low-temperature Daqu during Daqu-making process by metaproteomics, enzyme activity assay, and ELISA - Shuai Zhao; Yunfei Xia; Xing Chen; Yan Chen; Xuezhuang He; Menqing Cui; Yuchen Gao; Lei Wang; Jing Lu; Yawei Shi (Food Bioscience, 2026)

Efficient removal of N-nitrosodimethylamine and triclosan by nFe@Fe3O4 nanocomposites: Enhanced generation of active hydrogen atoms - Ying Han; Wanqing Zhao; Xiaoping Zheng; Chuwei Li; Lingyun Tang; Tengfei Zhang; Yawei Xie; Hongyuan Liu (Journal of Environmental Chemical Engineering, 2026)

An exploration into the transplacental transfer of microplastics through placental transporters - Binbin Guo; Yawei Wang; Weilin Wang; Ruining Guan; Dongquan Li; Qiyue Wang; Chunyan Zhao (Journal of Environmental Sciences, 2026)

Scale-dependent divergent response of soil respiration and its variation under grazing and reduced precipitation in a sandy Pinus sylvestris var. mongolica plantation - Zi Li; Xu Han; Hengming Zhang; Jiang Zhao; Xiang Li; Guochuang Zhang; Yawei Wei; Shengjin Qin (Journal of Soils and Sediments, 2026)

CLEC14A mediates trophoblast dysfunction in unexplained miscarriage by disrupting the cAMP/ERK signaling pathway - Jianing Wang; Yawei Shao; Linlin Zhou; Ruyue Ma; Shunli Dong; Ruiheng Zhao (Journal of Molecular Histology, 2026)

Nearshore bathymetry estimation from SAR imagery based on the adaptive window guided by local wave direction - Lijie Diao; Yongsheng Xu; Yawei Zhao; Haimei Mo; Yanlei Du; Xiaolan Qiu; Jinsong Chong (International Journal of Remote Sensing, 2026)

Enhanced reduction of 3-chloronitrobenzene by sulfidated microscale zero-valent iron: Performance and mechanism in anaerobic and aerobic systems - Ying Han; Chuwei Li; Qingjie Lu; Xinhui Ye; Wanqing Zhao; Yawei Xie; Haijiao Xie; Hongyuan Liu (Process Safety and Environmental Protection, 2026)

Investigating the impact of different abuse methods on the thermal runaway behavior of lithium batteries under high-rate charge and discharge conditions - Yajun Huang; Weifeng Xu; Xiongqi Shen; Yinquan Zhao; Yang Cao; Wei Bai; Junling Wang; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2026)

Human thermal responses to non-uniform cooling from intermittently operated split air conditioners - Haiyan Yan; Yawei Li; Thomas Parkinson; Stefano Schiavon; Hui Zhang; Ruiji Sun; Shengkai Zhao; Wei Zhao; Zhen sun; Fangning Shi (Building and Environment, 2026)

Parental HFPO-TA exposure induces intergenerational reproductive toxicity and DNA methylation alterations in zebrafish - Shasha Dong; Xiaohui Zhao; Xuan Ren; Jing Zhang; Zhibo Liu; Dan Yang; Ning Ji; Yawei Shi; Ya Sun; Guanghui Ding (ENGINEERING Environment, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Untargeted metabolomics-based investigation of amino acid effects on antimicrobial peptides production in Paenibacillus ehimensis HD 8-3 fermentation - Chengling Feng; Jiapei Zhang; Yunfei Si; Zhen Zhao; Yawei Ning; Zhixin Wang (Food Bioscience, 2026)

Applications of machine learning-based quantitative structure activity relationship (ML-QSAR) models in environmental science - Chao Chen; Yujia Tan; Yawei Liu; Miaomiao Sun; Zhiquan Wang; Xiangyong Zheng; Zhemin Shen; Min Zhao (Environmental Research, 2026)

Nutrient recovery from source-separated urine and urease inhibition during evaporation by a combination of salt, absorbent material, and dehumidification - Weikun Chen; Huijun Xiang; Chun Chen; Lanyue Feng; Ke Bei; Yawei Liu; Min Zhao; Xiangyong Zheng (Chemical Engineering Journal, 2026)

Nanopolystyrene and chrysene-induced gill damage in fish - Rahma Sakina Said Aly; Yawei Shen; Jinliang Zhao; Tiantian Chen; Xiaowu Chen (Aquaculture, 2026)

Novel enhanced network integrating transformations of DOM and microorganisms (ENITM) elucidates microbial-driven transformation pathways in estuarine sediments - Shiyang Yu; Jitao Lv; Xindong Ma; Lu Jiang; Qiurui Zhang; Tianyu Chen; Han Fang; Dong Cao; Lixia Zhao; Yawei Wang (Water Research, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Corrigendum to “Genomic and functional characterization of the lect2 gene from Siniperca chuatsi” [Fish Shellfish Immunology 107 (2020) 146–155] - Yawei Shen; Ming Cao; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen; Yanhui Bi (Fish & Shellfish Immunology, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Performance analysis of seismic mitigation by replacing foundation soil with a periodic structure for nuclear power structures considering SSI - Zequan Sun; Yawei Duan; Mi Zhao; Zhidong Gao; Di Yao; Lihua Wu; Guoliang Zhang; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Cardiac targeted delivery of Maresin 1 nanomedicine rescues microvascular obstruction after myocardial infarction - Yawei Zhao; Jing Zhang; Xiaohan Fan; Yue Cai; Wenting Du; Ziyi Yu; Biao Xu; Xuan Sun (Chemical Engineering Journal, 2026)

Molecular-scale mechanism of extracellular protein over-flocculation for sewage sludge dewatering by polyacrylamide - Minmin Liu; Jiesi Zhang; Yawei Zhao; Wei Wang; Huihui Zhang; Wenzheng Yu (Water Research, 2025)

Elaborating PFAS characteristics for Chinese electroplating industry by target and nontarget analysis - Bo-Xuan Zhang; Xiang-Zhou Meng; Bao-Cang Han; Zhen Zhao; Qin-Wen He; Cun-Di Ma; Qinghe Zhu; Jie Yang; Haiyan Qin; Yawei Wang (Water Research, 2025)

A multi-target QSAR model for simultaneously predicting the rate constants of reactions across multiple oxidation systems - Yawei Liu; Zhiquan Wang; Xiangyong Zheng; Min Zhao; Zhemin Shen (Journal of Hazardous Materials, 2025)

The inhibitory potential effect of CMC-Na on PhIP, Harman, and Norharman formation in low-NaCl fried beef patties under repeated freeze-thaw cycles - Yi Zhao; Pinghua Deng; Keying Zhang; Ruoxi Ma; Shuang Teng; Yawei Zhang (Food Chemistry, 2025)

Involvement of two-component system CseB-C in differential regulation of rapamycin and elaiophylin biosynthesis in Streptomyces rapamycinicus - Yawei Zhao; Shangping Jin; Pan Wang; Yuan Wang; Na Liu; Aimei Liao; Zhe Sun; Yinhua Lu; Hailong Tian (Food Bioscience, 2025)

Reversibility of the reproductive toxicity induced by hexafluoropropylene oxide trimer acid (HFPO-TA) in adult zebrafish (Danio rerio) - Dan Yang; Xuan Ren; Xiaohui Zhao; Shasha Dong; Xiaoying Li; Yawei Shi; Ya Sun; Guanghui Ding (Aquatic Toxicology, 2025)

Unraveling the health contributions of five key bioactives in virgin olive oil: A dose-based comparative review - Yunfei Huang; Wenqing He; Mengyao Zhao; David Julian McClements; Yawei Xu; Lu Li; Wanyi Dong; Xueqin Hu; Chunmei Li (Trends in Food Science & Technology, 2025)

The effect of fluid saturation on the elastic properties of coal measure rocks under confining pressure - Fei Gong; Guangui Zou; Suping Peng; Zhaoji Zhang; Hao Chen; Yawei Zhao (Journal of Applied Geophysics, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Energy-force coupling in interfacial solar vapor generation: A pathway to sustainable salt management - Yihong Liu; Yawei Yang; Bowen Liu; Qi Zhao; Yuyao Shen; Mengyuan Qiang; Yong Ma; Wenxiu Que (Desalination, 2025)

The inhibition potentiality of sodium carboxymethyl cellulose on PhIP, Harman, and Norharman formation of fried beef patties at low NaCl level - Yi Zhao; Pinghua Deng; Ruoxi Ma; Shuang Teng; Hang Lu; Zheng Liu; Haotian Yu; Yawei Zhang (Meat Science, 2025)

Water erosion control through vegetation restoration: Mechanisms and contributions of vegetation components in Robinia Pseudoacacia forests - Yang Li; Yawei Hu; Jiongchang Zhao; Jianjun Zhang (CATENA, 2025)

Measurement and modeling of canopy interception loss of evergreen, deciduous and mixed forests in a subhumid watershed on the Loess Plateau, China - Jiongchang Zhao; Yang Yu; Yawei Hu; Matthias Beyer; Jianjun Zhang (Journal of Hydrology, 2025)

Investigation on the inhibition mechanism of thermal runaway propagation in high-rate cycling lithium-ion pouch cells - Yajun Huang; Xiongqi Shen; Yinquan Zhao; Junling Wang; Yang Cao; Wei Bai; Yu Fan; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2025)

Mechanisms of antifungal activity of ehimensin F6 produced by Paenibacillus ehimensis HD against Penicillium expansum - Yuqing Huang; Dandan Liu; Yahui Liu; Ziwei Jia; Tengteng Zhao; Zhen Zhao; Yawei Ning; Xiaohui Liang; Zhixin Wang (International Journal of Food Microbiology, 2025)

Pathways of 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) inhibited by basic amino acids in the glucose/ creatinine/ phenylalanine model system - Pinghua Deng; Yi Zhao; Shuang Teng; Keying Zhang; Yawei Zhang (Food Chemistry, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Sucrose laurate and nisin synergistically inhibit Bacillus subtilis by multiple antibacterial targets and play promising application potential in bread preservation - Danya Tong; Panpan Han; Mingrui Li; Zhixin Wang; Zhen Zhao; Yingmin Jia; Yawei Ning (Food Chemistry, 2025)

Mechanism investigation into static magnetic field effects on enhancing surfactin productivity by Bacillus subtilis - Yamei Jin; Sirui Chen; Qiyan Zhao; Na Yang; Yawei Ning; Xueming Xu (Food Bioscience, 2025)

The Combined Effect Between SEPS1 Genetic Polymorphisms and Exposure to Metals on the Risk of Gestational Diabetes Mellitus - Weiwei Wu; Yulin Li; Weixuan Hu; Jing Zhao; Bole Zhang; Yongliang Feng; Yawei Zhang; Suping Wang (Biological Trace Element Research, 2025)

Atmospheric fronts detection and cold/warm type determination based on wind field retrieval from SAR imagery - Xianen Wei; Jinsong Chong; Yawei Zhao; Wenjia Zhao; Yongsheng Xu (International Journal of Remote Sensing, 2025)

Ancient genomes shed light on the long-term genetic stability in the Central Plain of China - Hao Ma; Yawei Zhou; Rui Wang; Fei Yan; Haodong Chen; Limin Qiu; Jing Zhao; Li Jin; Chuan-Chao Wang (Science Bulletin, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Ultrasensitive and high selectivity detection of fibrin using Y-shaped DNA-homing peptide doped probe on localized surface plasmon resonance platform - Yawei Chen; Yuanfu Zhang; Xue Zhao; Wenyu Xu; Shuhao Wang (Analytica Chimica Acta, 2025)

Insight into the keystones of Chinese broad bean paste fermentation: Brewing techniques, chemosensory characteristics, and microbial community - Shuai Zhao; Chang Hao; Chengtuo Niu; Jing Lu; Lei Wang; Yawei Shi; Qi Li (Trends in Food Science & Technology, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Interfacial evaporation and salt-blocking kinetics in Janus membrane for solar desalination - Haowei Hu; Jin Wang; Qi Zhao; Mengyuan Qiang; Qin Li; Lin Guo; Yawei Yang (Desalination, 2024)

Comprehensive characterization of the differences in metabolites, lipids, and volatile flavor compounds between Ningxiang and Berkshire pigs using multi-omics techniques - Qian Wang; Hu Gao; Yawei Fu; Yue Chen; Gang Song; Zhao Jin; Yuebo Zhang; Jie Yin; Yulong Yin; Kang Xu (Food Chemistry, 2024)

Optimal conditions for cryopreservation by vitrification of largemouth bass (Micropterus salmoides) embryos - Meng Zhang; Xiao Ma; Yuqing Han; Zerui Wang; Zhilin Jia; Dongcai Chen; Zhigang Qiao; Xiaotian Gao; Chunlong Zhao; Yawei Shen (Animal Reproduction Science, 2024)

Effects of inorganic sodium on the soot generation of coal particle: Insights with PLIF and DFT calculation - Yawei Song; Sheng Su; Zheng Zhao; Jingyan Wang; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Song Hu; Jun Xiang (Fuel, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

Thyroid disrupting effects and the developmental toxicity of hexafluoropropylene oxide oligomer acids in zebrafish during early development - Xiaohui Zhao; Xianghan Meng; Dan Yang; Shasha Dong; Jianhui Xu; Dezhi Chen; Yawei Shi; Ya Sun; Guanghui Ding (Chemosphere, 2024)

Enhanced treatment of pyridine wastewater by a hybrid membrane biofilm reactor: Simultaneous biodegradation of pyridine and removal of nitrogen - Jingyi Zhang; Yawei Tian; Zhan Wang; Mengmeng Yang; Yong Wang; Han Gao; Zimiao Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xuanwei Zhao; Yue Wu; et al. (Process Safety and Environmental Protection, 2024)

High throughput identification of carbonyl compounds in natural organic matter by directional derivatization combined with ultra-high resolution mass spectrometry - Shiyang Yu; Shanshan Tang; Jitao Lv; Feifei Li; Zichun Huang; Lixia Zhao; Dong Cao; Yawei Wang (Water Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Assessment major NOx sources to nitrate of TSP around the Danjiangkou reservoir using isotopes and a Bayesian isotope mixing model - Chunyan Xiao; Yimeng Sun; Tongqian Zhao; Guizhen Wang; Pengbo Li; Yawei Zhao; Feihong Chen (Atmospheric Pollution Research, 2024)

The application of chitosan quaternary ammonium salt to replace polymeric aluminum ferric chloride for sewage sludge dewatering - Minmin Liu; Sajid Rashid; Wei Wang; Huihui Zhang; Yawei Zhao; Xingmin Fu; Zhaoyang Su; Nigel Graham; Wenzheng Yu (Water Research, 2024)

Long‒term trends in surface thermal environment and its potential drivers along the urban development gradients in rapidly urbanizing regions of China - Chengyu Zhao; Hongkai Zhu; Shuyi Zhang; Ziwen Jin; Yiwen Zhang; Yawei Wang; Yadie Shi; Jianhui Jiang; Xiaoyong Chen; Min Liu (Sustainable Cities and Society, 2024)

Experimental study on the dynamic responses of harbour seal whiskers in the wake of caudal fin - Hanghao Zhao; Zhimeng Zhang; Weilin Chen; Yawei Zhao; Edward Yaw Sefah; Chunning Ji; Dekui Yuan (Ocean Engineering, 2024)

Experimental study on flow-induced vibrations of an equilateral triangular prism with a high mass ratio - Yawei Zhao; Zhimeng Zhang; Chunning Ji; Hanghao Zhao; Weilin Chen (Ocean Engineering, 2024)

Characteristics of advanced anaerobic digestion sludge-based biochar and its application for sewage sludge conditioning - Qian Chen; Xingmin Fu; Jiawei Wang; Yawei Zhao; Wei Wang; Abdul Ghaffar Memon; Huihui Zhang; Yang Wen (Bioresource Technology, 2024)

Domestication affects nitrogen use efficiency in foxtail millet - Yufeng Deng; Yawei Chen; Taiji Kou; Yukun Bo; Meicheng Zhao; Feng Zhu (Euphytica, 2024)

The silent threat: Nanopolystyrene and chrysene pollutants disrupt the intestinal mucosal barrier, new insights from juvenile Siniperca chuatsi - Tiantian Chen; Rahma Sakina Said Aly; Yawei Shen; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Degradation metabolic pathway of low-rank coal using single hydrolytic bacteria - Daping Xia; Yunxia Niu; Jixian Tian; Xianbo Su; Guoqin Wei; Kuo Jian; Zhenzhi Wang; Yawei Zhang; Weizhong Zhao (Fuel, 2024)

Exquisite visualization of mitophagy and monitoring the increase of lysosomal micro-viscosity in mitophagy with an unusual pH-independent lysosomal rotor - Rui Yang; Wei He; Changxin Zhu; Xifeng Yang; Yawei Kuang; Tao Zhu; Jingyang Xu; Yuang Zhao; Tingwang Jiang; Yushen Liu; Mengmeng Wei (Analytica Chimica Acta, 2024)

An improved current retrieval method for ice-edge eddies from multi-sensor remote sensing image sequences - Xue Yang; Jinsong Chong; Yawei Zhao; Wenjia Zhao (International Journal of Remote Sensing, 2024)

Nanoplastics and chrysene pollution: Potential new triggers for nonalcoholic fatty liver disease and hepatitis, insights from juvenile Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Zequn Huang; Yifeng Gu; Qun Wei; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Enhanced fluid mixing using a novel multi-stage static pipeline mixer: Numerical simulation and mechanism analysis - Jiaheng Zhao; Xing Li; Zedong Lu; Wenjun Chi; Zhibin Wang; Yawei Chen (Journal of Water Process Engineering, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Comprehensive visual information acquisition for tomato picking robot based on multitask convolutional neural network - Xiaoqiang Du; Zhichao Meng; Zenghong Ma; Lijun Zhao; Wenwu Lu; Hongchao Cheng; Yawei Wang (Biosystems Engineering, 2024)

A critical review on the bioaccumulation, transportation, and elimination of per- and polyfluoroalkyl substances in human beings - Yao Lu; Ruining Guan; Nali Zhu; Jinghua Hao; Hanyong Peng; Anen He; Chunyan Zhao; Yawei Wang; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2024)

Low vaporization enthalpy hydrogels for highly efficient solar-driven interfacial evaporation - Qi Zhao; Yawei Yang; Benxin Zhu; Zuyi Sha; Hui Zhu; Zhixin Wu; Fahad Nawaz; Yumeng Wei; Lingdi Luo; Wenxiu Que (Desalination, 2023)

Mesopore-enhanced graphene electrodes with modified hydrophilicity for ultrahigh capacitive deionization - Ting Yang; Hongmei Zhang; Linpei Guo; Jing Wang; Zhiyuan Guo; Yawei Du; Jie Liu; Yingying Zhao; Panpan Zhang; Zhi-Yong Ji (Desalination, 2023)

Impacts of exposure to nanopolystyrene and/or chrysene at ambient concentrations on neurotoxicity in Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yawei Shen; Tingwen Cui; Zonglin Yang; Yufei Liu; Jinliang Zhao; Xiaowu Chen (Chemosphere, 2023)

Numerical validation of analytical solutions for tunnels and their applicability evaluation index - Yawei Duan; Jingqi Huang; Mi Zhao; Xu Zhao; Huifang Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

Quantitative generation of ROS and their effective photocatalytic antibacterial activity of high-intensity universal P25 network films: The role of ROS - Jin Xu; Chengzhuo Yu; Silong Wang; Li Xiong; Fanglan Geng; Jitao Lv; Lixia Zhao; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Analytical solutions for stresses and displacements of tunnels under static and seismic loading - Yawei Duan; Jingqi Huang; Xu Zhao; Mi Zhao; Huifang Li; Xiuli Du (Computers and Geotechnics, 2023)

Coating TiO2 with MIL-101(Fe) to decarboxylate D-Glu and D-MeAsp of microcystin-LR from HA-rich water: Diminishing the inhibitory effect of humic acids - Yarui Wang; Chengzhuo Yu; Sen Wang; Jin Xu; Fanglan Geng; Silong Wang; Jitao Lv; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2023)

Investigation with ESI FT-ICR MS on sorbent selectivity and comprehensive molecular composition of landfill leachate dissolved organic matter - Qiurui Zhang; Jitao Lv; Anen He; Dong Cao; Xiaosong He; Lixia Zhao; Yawei Wang; Guibin Jiang (Water Research, 2023)

Developmental Toxicity and Cardiotoxicity Induced by PFOS and its Novel Alternative OBS in Early Life Stage of Zebrafish (Danio rerio) - Dan Yang; Xiaohui Li; Shasha Dong; Xiaohui Zhao; Xiaoying Li; Meng Zhang; Yawei Shi; Guanghui Ding (Water, Air, & Soil Pollution, 2023)

Reaction mechanism of NO and SO2 Co-removal by calcium hydroxide - Angran Zhao; Yongqiang Han; Zhipeng Wang; Pengfei Li; Yawei Xu; Ruiming Yang; Huiling Tong (Journal of Environmental Chemical Engineering, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

Pretreatment of moso bamboo with p-toluenesulfonic acid for the recovery and depolymerization of hemicellulose - Meixin Wang; Yawei Zhan; Jiayue Zhao; Zhiqiang Li (Bioresource Technology, 2023)

Overview of the main biological mechanisms linked to changes in periodontal ligament stem cells and the inflammatory microenvironment - Xuetao Zhao; Hongbing Lin; Tong Ding; Yawei Wang; Na Liu; Yuqin Shen (Journal of Zhejiang University-SCIENCE B, 2023)

Analytical solution for the temperature field of an elliptical tunnel in cold regions - Yanhu Zhao; Jing Zhang; Linjing Li; Taotao Hu; Yawei Zhao (Cold Regions Science and Technology, 2023)

Flood Risk Quantification, Transmission, and Propagation Analysis for Flood Water Utilization of Parallel Reservoirs - Wei Ding; Chi Zhang; Jie Lin; Xi Zhao; Yawei Ning; Huicheng Zhou (Journal of Hydrology, 2023)

An overview on the two-component systems of Streptomyces coelicolor - Shangping Jin; Ming Hui; Yinhua Lu; Yawei Zhao (World Journal of Microbiology and Biotechnology, 2023)

From bitter to delicious: properties and uses of microbial aminopeptidases - Yawei Wang; Puying Zhao; Ying Zhou; Xiaomin Hu; Hairong Xiong (World Journal of Microbiology and Biotechnology, 2023)

Innovative calcium-doped layered yttrium hydroxides for rapid and efficient removal of fluoride from aqueous solutions: Insight into adsorption mechanism - Ying Liang; Fengjie Chen; Meng Zhang; Lufeng Chen; Yu Xia; Zhen Zhou; Bolei Chen; Lixia Zhao; Yong Liang; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Novel strategies and approaches toward toxicity assessment: a key factor for safety assessment and management of per- and polyfluoroalkyl substances - Yao Lu; Chunyan Zhao; Hanyong Peng; Jinghua Hao; Chunyang Liao; Yong Liang; Yawei Wang; Guibin Jiang (Science Bulletin, 2023)

DLGAP1-AS2 promotes estrogen receptor signalling and confers tamoxifen resistance in breast cancer - Xiaoli Liang; Yang Zhao; Zeng Fang; Nan Shao; Duanyang Zhai; Mengmeng Zhang; Liang Yu; Yawei Shi (Molecular Biology Reports, 2022)

Research on Surrounding Rock Control Technology of Gob-Side Entry Retaining by Directional Roof Cutting in a Deep Coal Mine - Haojie Xue; Shibao Shen; Haoran Lu; Renbao Zhao; Peishuai Li; Yawei Zhao; Qibin Jiang; Longjiang Wang; Beizhan Fan; Tao Qin (Geotechnical and Geological Engineering, 2022)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Promoter methylation and expression of the rassf4 gene in Nile tilapia ( Oreochromis niloticus ) - Yawei Shen; Huiyang Li; Min Zhou; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Journal of Fish Biology, 2021)
Oreochromis niloticus RAS‐association domain family 4 ( rassf4 ) was specifically expressed in the ovaries. Immunohistochemistry results showed that Rassf4 was located in follicular cells. The methylation percentages of the promoter region (−734/−1012) of rassf4 in the ovaries and testes were 13.28% and 92.85%, respectively. Deleting the fragment of −734 to −1012 sites significantly reduced the basal activity of the rassf4 promoter to 62.33%, which indicated that this region was important for the transcription of the rassf4 gene. This study lays the foundation for further research on the function of fish rassf4 .

Research on the mechanical properties and electrical conductivity of cement mortar based on recycled nano-iron boride - Wei He; Zhinan Jiao; Yawei Wang; Jihang Xu; Qingxin Zhao (Waste Disposal & Sustainable Energy, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Tocilizumab for treating COVID-19: a systemic review and meta-analysis of retrospective studies - Meng Zhao; Jieyu Lu; Yihu Tang; Yawei Dai; Jingxin Zhou; Yanhu Wu (European Journal of Clinical Pharmacology, 2021)

Multiplex genome editing using a dCas9-cytidine deaminase fusion in Streptomyces - Yawei Zhao; Jinzhong Tian; Guosong Zheng; Jun Chen; Chuanwen Sun; Zhongyi Yang; Andrei A. Zimin; Weihong Jiang; Zixin Deng; Zhijun Wang; Yinhua Lu (Science China Life Sciences, 2020)

Expression profile analyses of mettl8 in Oryzias latipes - Wei Pang; Ziwei Zhao; Yawei Shen; Yanhui Bi; Yifeng Gu; Xiaowu Chen (Fish Physiology and Biochemistry, 2020)

Antimicrobial Peptide JH-3 Effectively Kills Salmonella enterica Serovar Typhimurium Strain CVCC541 and Reduces Its Pathogenicity in Mice - Lei Wang; Xueqin Zhao; Xiaojing Xia; Chunling Zhu; Wanhai Qin; Yanzhao Xu; Bolin Hang; Yawei Sun; Shijun Chen; Huihui Zhang; Jinqing Jiang; Jianhe Hu; et al. (Probiotics and Antimicrobial Proteins, 2019)

5-FU preferably induces apoptosis in BRAF V600E colorectal cancer cells via downregulation of Bcl-xL - Tongfei Shi; Mohan Gao; Meihui He; Fengli Yue; Yawei Zhao; Madi Sun; Kan He; Li Chen (Molecular and Cellular Biochemistry, 2019)

Irf3 from mandarin fish thymus initiates interferon transcription - Xiaowu Chen; Yawei Shen; Minglin Wu; Jinliang Zhao (Fish Physiology and Biochemistry, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Metals compositions of indoor PM2.5, health risk assessment, and birth outcomes in Lanzhou, China - Yaqun Zhang; Suzhen Cao; Xiaoying Xu; Jie Qiu; Mingxia Chen; Dennis Wang; Donghong Guan; Chengyuan Wang; Xiao Wang; Bowen Dong; Huang Huang; Nan Zhao; et al. (Environmental Monitoring and Assessment, 2016)

Effects of vegetation and soil texture on surface soil moisture retrieval using multi-temporal optical and thermal infrared observations - Pei Leng; Xiaoning Song; Zhao-Liang Li; Yawei Wang; Di Wang (International Journal of Remote Sensing, 2015)

Forest carbon storage and tree carbon pool dynamics under natural forest protection program in northeastern China - Yawei Wei; Dapao Yu; Bernard Joseph Lewis; Li Zhou; Wangming Zhou; Xiangmin Fang; Wei Zhao; Shengnan Wu; Limin Dai (Chinese Geographical Science, 2014)

Land use effects on soil organic carbon, microbial biomass and microbial activity in Changbai Mountains of Northeast China - Xiangmin Fang; Qingli Wang; Wangming Zhou; Wei Zhao; Yawei Wei; Lijun Niu; Limin Dai (Chinese Geographical Science, 2014)

Risk of non-Hodgkin lymphoma and nitrate and nitrite from the diet in Connecticut women - Briseis A. Kilfoy; Mary H. Ward; Tongzhang Zheng; Theodore R. Holford; Peter Boyle; Ping Zhao; Min Dai; Brian Leaderer; Yawei Zhang (Cancer Causes & Control, 2010)

Genetic variation in N-acetyltransferases 1 and 2, cigarette smoking, and risk of non-Hodgkin lymphoma - Briseis A. Kilfoy; Tongzhang Zheng; Qing Lan; Xuesong Han; Theodore Holford; David W. Hein; Qin Qin; Brian Leaderer; Lindsay M. Morton; Meredith Yeager; Peter Boyle; Ping Zhao; et al. (Cancer Causes & Control, 2010)